Collaborative Governance in Corruption Alleviation: Handling Public Reports in South Sumatra Local Government - Harahap, Ferry; Sobri, Kiagus Muhammad; Putra, Raniasa; Najib, Abdul (Green Publisher Indonesia, 2025)
The cooperation agreement (MoU) between the Ministry of Home Affairs (Kemendagri), the Criminal Investigation Branch of the National Police, and the Attorney General's Office (Kejagung) aims to conduct investigative audits on indications of corruption. The results of the audit by APIP found that the overpayment must be returned to the state treasury, which has the potential to stop the investigation of corruption cases. However, the option of replacement within 60 days does not provide a deterrent effect to the perpetrator. This study analyzes the collaboration in the implementation of the agreement policy in South Sumatra, using the theory of Good Governance and a collaborative governance approach. The methods used include interviews, observations, and documentation. The findings show that the implementation of policies to overcome public reports about corruption in the South Sumatra Regional Government has not been effective. Although there are no problems in the Collaborative Governance aspect, the effectiveness of implementation is hampered by the process and the impact of policies. Therefore, the Collaborative Governance model in handling corruption can only achieve effective results if all dimensions of policy implementation are met and synergy, transparency, integrity, and accountability between collaborating institutions are built.